Pembelajaran Pendidikan Agama Islam yang Kontekstual dan Interaktif: Pengaruh Contextual Teaching and Learning Berbantuan Wordwall terhadap Motivasi Belajar - Achmad Fadli Romadhon; Syaiful Anwar; M. Indra Saputra (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
Students’ learning motivation in Islamic Religious Education remains a persistent concern when the instructional process is predominantly characterized by conventional methods, limited interactivity, and insufficient connection between learning materials and students’ real-life experiences. This study aims to analyze the effect of the Contextual Teaching and Learning model assisted by Wordwall media on students’ learning motivation in Islamic Religious Education at SMP Taman Siswa Bandar Lampung. This research employed a quantitative approach using a quasi-experimental method with a Posttest-Only Control Group Design. The research population consisted of 60 eighth-grade students, with Class VIII A serving as the experimental group comprising 30 students and Class VIII B as the control group comprising 30 students. Data were collected through a Likert-scale learning motivation questionnaire administered after the treatment. The data were analyzed through normality testing, homogeneity testing, and an independent samples t-test using SPSS. The findings indicate that the data were normally distributed and homogeneous. The t-test results revealed a significance value of 0.001 < 0.05, with a mean difference of 3.60860. Therefore, the Contextual Teaching and Learning model assisted by Wordwall media has a significant effect on students’ learning motivation in Islamic Religious Education. These findings suggest that the integration of contextual learning and interactive digital media can serve as a more engaging, meaningful, and relevant instructional strategy aligned with students’ learning needs.